HUBUNGAN MOTIVASI DAN PERHATIAN ORANG TUA DENGAN PRESTASI BELAJAR GEOGRAFI SISWA SMAN 10 KOTA PALANGKA RAYA - Dedy Norsandi; Kukuh Wurdianto; Evi Fitriana (Universitas Negeri Gorontalo, 2022)
Student's learning achievement is influenced by internal and external factors. This research aims to determine the correlation between learning motivation and parental attention with student achievement in geography subjects at SMAN 10 Palangka Raya City. This study uses a quantitative approach. The type of research is ex-post facto. Based on the variables, this research is a correlational study to determine the relationship between motivation and parental attention with geography learning achievement. The population of this research was 351 students of SMAN 10 Palangka Raya City, with a sample of 100 students. Data collection techniques were carried out using questionnaires and documentation. Data analysis used analysis prerequisite test which consisted of normality test, linearity test and multicollinearity test. The data analysis method uses simple linear correlation analysis and multiple linear correlations. The results showed that: there is a positive relationship between learning motivation and student geography learning achievement, where t=3,900 is greater than t0.05(98) = 1.99, so H1 can be accepted; There is a positive relationship between parental attention and students' geography learning achievement where t=4.325 is greater than t0.05(98) = 1.99 (ttable) or P-value = 0.000 less than 0.05 so that H2 can be accepted; and between learning motivation and parental attention is positively related to the geography learning achievement of SMAN 10 Palangka Raya students where F=17,038 is greater than F0.05(98) = 3.13 or P-value = 0.000 less than 0.05 so H3 can be accepted